Entrepreneurial Skills Reinforcement Model in “Merdeka Belajar Kampus Merdeka” Entrepreneurship at University of Merdeka Malang - Aris Siswati; Boge Triatmanto; Sunardi Sunardi (Jurnal Penelitian, 2021)
In achieving long-term goals and specific targets researchers will develop a model ESRM (entrepreneurial Skill Reinforcement Model) in order to create a strong competitive edge in the face of the complex economic conditions. The existence of limited information regarding training and education that strengthens entrepreneurial skills can affect the quality of an entrepreneur. This study aims to cluster and need analyze the interests of students in entrepreneurship at the University of Merdeka Malang. The method that will be used in this research is using the clustering method, where at this stage the student's entrepreneurial interest will be clustered, then a need assessment is carried out and then the model design is carried out according to the student's needs. In the next stage, a model for strengthening entrepreneurial skills was designed and then improved with focus group discussions and expert tests so that the model became feasible and suitable to be applied. Then it will be tested in a trial class to test the effectiveness of the model. The results of the model's feasibility analysis show that there is a strong agreement between experts and practitioners on the feasibility of the developed model. In addition, based on the effectiveness test, the research product in the form of ESRM is categorized as effective for increasing entrepreneurial skills instudents.